PENINGKATAN KETERAMPILAN UNGGAH-UNGGUH RAGAM KRAMA MELALUI MODEL PEMBELAJARAN ROLE PLAYING PADA SISWA KELAS IV SD N KLETERAN 3 - Masjid, Akbar Al; Nugraheni, Salsabila (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
This article aims to describe the increase in upload-upload skills of various manners through the role-playing learning model for grade IV students of SD Negeri Kleteran 3 Grabag. This action hypothesizes that the role-playing learning model can improve speaking skills, especially regarding the upload-upload variety of manners. Data collection techniques in this study were carried out using observation, interviews, tests, and documentation. The observations were analyzed by determining agreement on the assessment of speaking skills uploading a variety of student manners. Analysis of the data used is quantitative and comparative descriptive analysis. The results showed how applying the role-playing method to Javanese language skills subjects from pre-action to cycle I and cycle II increased motivation. The average value of speaking skills using poultry-really diverse students in the first cycle 75.47 and increased in the second cycle to 86.88. Students who completed in the first cycle were 18 students with a percentage of 56% and in the second cycle students completed as many as 28 students with a percentage of 87,5%. Based on this research, learning using a variety of student manners increased through the role-playing method.